DIASTOLIC FUNCTION IS IMPAIRED IN DOGS WITH MYXOMATOUS MITRAL VALVE DISEASE - CAMACHO, R. R.; SOUSA, M. G.; FRANCO, R. P.; GAVA, F. N.; CAMACHO, A. A. (Ars Veterinaria, 2016)
Myxomatous mitral valve disease (MMVD) is the most common cardiac disease in dogs, and the echocardiogram is required to investigate the degree of remodeling and the intensity of cardiac dysfunction. Therefore, the aim of this study was to assess diastolic function in dogs with MMVD in different stages, and to compare them with healthy animals. This study enrolled 12 mature dogs with MMVD, which were subdivided in two groups: stage B2 (n=7) and stage C (n=5). Also, 9 healthy adult dogs were recruited to serve as controls. Several echocardiographic data were obtained for the assessment of diastolic function, as well as some parameters intended to evaluate the cardiac structure and systolic function, which were used to search for correlations with the diastolic parameters. Concerning diastolic function, a significant difference was found to exist between groups for the peak velocity of left ventricular slow filling, the isovolumic relaxation time, and the mitral annular velocities at early and late diastole. These findings are associated with the structural and hemodynamic changes ascribed to the progression of MMVD and the intensification of congestive heart failure. The indices calculated from the peak velocity of left ventricular rapid filling and the mitral annular velocities obtained at early and late diastole also differed between healthy and diseased dogs. Because some of these indices are surrogates for left ventricular filling pressure and the congestive status of the patient, the results of this study are supportive of the relationship between the progression of MMVD and diastolic impairment, besides the eccentric structural remodeling attributable to this cardiac disease.